Contraception Reduces Breast Milk Protein Level of Breastfeeding Mothers in Jember, East Java, Indonesia - Nuzula Irfa Nuriana; FX. Ady Soesetijo; Candra Bumi (Humanistic Network for Science and Technology (HNST), 2020)
The protein level of breast milk affected the growth and development of infants. Protein has special function which is irreplaceable by other nutrients to form and protect the body cells. Protein also plays a role as antibody, functions as the body defense mechanism against various diseases and infections. Infant death in Indonesia is mostly caused by respiratory tract infections and diarrhea. Breastfeeding can help to prevent the occurrence of morbidity and mortality of infants and toddlers in which the breast milk contains many essential nutrients needed by the body, one of them is protein. The aim of this research was to analyze the effect of contraception on breast milk protein level of breastfeeding mothers in Jember regency. The design of this research was observational analytic with cross sectional approach, using statistic test of logistic regression. The result of the research showed that the effect of contraception on the protein level of breast milk obtained p-value=0.021 with Exp(B)=566.263. Based on the research, it can be concluded that there was an effect of contraception on breast milk protein level. Keywords: infection; breastmilk protein; contraception